Enhancing Community Knowledge on the Utilization of Family Medicinal Plants (TOGA) for Disease Prevention - Fitratul Aqidah; Jihan Pratiwi Ika Antasari; Ria Ramadhani Wahid; Muh Yudha Joe Satriani; Wahid Wahid; Hezron Alhim Dos Santos (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Rural communities often face challenges in maintaining health due to limited access to healthcare services and low awareness of healthy lifestyles. One potential solution is the utilization of Family Medicinal Plants (TOGA) as an accessible, community-based disease prevention strategy. This community engagement activity was implemented through the Griya SIPAKABERU Environmental Health Program, aiming to improve community knowledge and skills in identifying, processing, and utilizing TOGA. The methods included interactive education sessions through lectures, group discussions, and hands-on practice on plant types, health benefits, and processing techniques. Evaluation was conducted using pre- and post-tests with 13 respondents, including housewives and village health cadres. Results indicated a significant improvement in average scores from 54.84 to 91.23, representing a 55% increase. Participants also expressed strong enthusiasm for cultivating TOGA in their home gardens as a form of self-care and preventive health practice. The program effectively enhanced community awareness and understanding of TOGA utilization while promoting health independence based on local resources. Sustained support from village authorities and cross-sector collaboration is essential to ensure the long-term impact of the program on rural health and community well-being.